THE IMPORTANCE OF THE IDEA OF TOLERANCE IN THE DEVELOPMENT OF SOCIETY - Dilfuza Odilovna Inomova (American Journals Publishing, 2023)
Tolerance as a socio-political phenomenon originated from ancient times, it opened the world to the formation of a welfare society and a system of associated values, and strengthened such values as freedom, equality, respect for a person, for his person.
Keywords: tolerance, idea, Society, Development, civic Institute, freedom, equality